Analisis Disparitas Pendapatan Regional di Provinsi Aceh - Nur Aidar; Ramadhan Syahputra (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2015)
This study aimed to analyze the level of income disparity in the district / city in the province of Aceh. The study used secondary data from 2002 through 2011. Theil entropy index is used to look at the level of disparity between districts / cities in Aceh province which have been grouped into three groups of regions of the North-East region, Central Aceh region, and the South-West region.  The results showed that the per capita income disparities between districts / cities that occur between the Aceh region is relatively high. This study also found that income disparity with Theil entropy index is highest in the North-East region of Aceh, followed by the Central region of Aceh, and the smallest in the South-West region of Aceh. The study recommends: (1) Local government as policy makers should not only focus on economic growth but also to be able to do a more equitable income distribution, (2) Pressing the population growth rate becomes essential to keep the level of income disparity in the area can be minimize.